LEGO‐NMR Spectroscopy: A Method to Visualize Individual Subunits in Large Heteromeric Complexes1. Issue 43 (14th August 2013) - Mund, Markus; Overbeck, Jan H.; Ullmann, Janina; Sprangers, Remco
<x xml:space="preserve">Abstract</x> Seeing the big picture: Asymmetric macromolecular complexes that are NMR active in only a subset of their subunits can be prepared, thus decreasing NMR spectral complexity. For the hetero heptameric LSm1–7 and LSm2–8 rings NMR spectra of the individual subunits of the complete complex are obtained, showing a conserved RNA binding site. This LEGO‐NMR technique makes large asymmetric complexes accessible to detailed NMR spectroscopic studies.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>